Effects of 12 months of detraining on health-related quality of life in patients receiving hemodialysis therapy - Costa Rosa, Clara Suemi [UNESP]; Giannaki, Christoforos D.; Krase, Argyro; Mplekou, Meropi; Grigoriou, Stefania S.; Stefanidis, Ioannis; Lavdas, Eleftherios; Pappas, Aggelos; Bloxham, Saul; Karatzaferi, Christina; Sakkas, Giorgos K. (Springer, 2020)
Purpose Limited data exist regarding the effects of detraining on functional capacity and quality of life (QoL) in the hemodialysis population. The aim of the current study was to assess whether the discontinuation from a systematic intradialytic exercise training program will affect aspects of health-related QoL and functional capacity in hemodialysis patients. Methods Seventeen hemodialysis patients (12 Males/5 Females, age 60.8 +/- 13.6 year) participated in this study. Patients were assessed for functional capacity using various functional capacity tests while QoL, daily sleepiness, sleep quality, depression and fatigue were assessed using validated questionnaires at the end of a 12-month aerobic exercise program and after 12 months of detraining. Results The detraining significantly reduced patients' QoL score by 20% (P = 0.01). More affected were aspects related to the physical component summary of the QoL (P < 0.001) rather than those related to the mental one (P = 0.096). In addition, the performance in the functional capacity tests was reduced (P < 0.05), while sleep quality (P = 0.020) and daily sleepiness scores (P = 0.006) were significantly worse after the detraining period. Depressive symptoms (P = 0.214) and the level of fatigue (P = 0.163) did not change significantly. Conclusions Detraining has a detrimental effect in patients' QoL, functional capacity and sleep quality. The affected physical health contributed significantly to the lower QoL score. It is crucial for the chronic disease patients, even during emergencies such as lockdowns and restrictions in activities to maintain a minimum level of activity to preserve some of the acquired benefits and maintain their health status.
Keywords: Hemodialysis; Exercise training; Detraining; Quality of life